Youth soccer players` physical activity levels during modified soccer games - Sinelnikov, O.; Chen, Y.-C. (Research Quarterly for Exercise and Sport, 2011)
Youth sports play a significant public health role as a provider of physical activity (PA) for children. The largest youth sports organization is U.S. Youth Soccer with 3.2 million players. The purpose of the study was to compare youth soccer players` moderate-to-vigorous physical activity (MVPA) during matches played according to U.S. Youth Soccer guidelines and during similar matches but without field boundaries. The participants in this study included 144 U6 youth soccer players (M age = 4.6 years; SD = .64) randomly assigned to 24 coed teams. The System for Observing Fitness Instruction Time (McKenzie, Sallis, & Nader, 1991) was used to record PA levels during matches. A counterbalanced design was used to mitigate carryover effects and a total of 72 matches were coded (36 with boundaries and 36 without). A 2 (age) x 2 (condition) repeated measures analysis of variance was conducted to compare the effect of the age of youth soccer players on their MVPA in matches played with and without boundaries. Playing matches without the boundaries increased MVPA for both 4- and 5-year-old soccer players with main effect of boundaries condition: F(1, 22) = 139.05, p < .0001, ç2 = .863. The interaction effect was not significant, F(1, 22) = 3.03, p = .96. The results suggest that allowing soccer players under the age of six to play matches without boundaries significantly increases their MVPA. It is therefore recommended that US Youth Soccer allow modification of law 9 (ball in and out of play) for U6 players.